2019
DOI: 10.1519/jsc.0000000000002425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Contrast Strength vs. Plyometric Training on Lower-Limb Explosive Performance, Ability to Change Direction and Neuromuscular Adaptation in Soccer Players

Abstract: The aim was to compare the effects of two differing 8-week in-season strength training programs (contrast strength training [CST] vs. plyometric training [PT]) on selected performance tests (5 and 40m sprints, S 4 X 5 m change of direction test, squat (SJ) and countermovement (CMJ) jumps , leg peak power on a cycle ergometer force-velocity test, 1-repetition maximal (1-RM) half squat, and electromyographic [EMG] activity of the vastus lateralis, vastus medialis and rectus femoris muscles during vertical jump t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 32 publications
7
67
2
9
Order By: Relevance
“…The significantly increased CMJ height due to the plyometric training in this study is in agreement with studies about the effect of short-term plyometric training (1,(15)(16)(17)(18)(19)). In the current study, the CMJ height was increased from 43.80 cm to 53.13 cm (21.3%) after 6-week plyometric training.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The significantly increased CMJ height due to the plyometric training in this study is in agreement with studies about the effect of short-term plyometric training (1,(15)(16)(17)(18)(19)). In the current study, the CMJ height was increased from 43.80 cm to 53.13 cm (21.3%) after 6-week plyometric training.…”
Section: Discussionsupporting
confidence: 92%
“…Arabatzi et al indicated a significant increase in CMJ height and a decrease in maximum knee angle after 8-week PT, while the hip angle was not significantly altered (15). Moreover, Hammami et al and Zubac et al found a significant increase in CMJ height due to 8-week PT (16,17). Adibpour et al found a significant increase in CMJ height due to eight weeks of combined plyometric and weight training for young female basketball players (18).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, it was seen that plyometric training group's and contrast strength training group's squat jump and counter movement jump performances post-test results were significantly higher than control group's post-test results. On the other hand, it was found that plyometric training group's agility performance post-test results were significantly higher than control group's agility performance post-test results (Hammami, Gaamouri, Shephard & Chelly, 2019).…”
Section: Discussionmentioning
confidence: 75%
“…A tabela 4 apresenta as características metodológicas e os principais resultados dos estudos incluídos na presente revisão. Os 7 primeiros estudos utilizaram o TP como intervenção, sem associação com outros métodos e avaliaram diferentes tipos de saltos representados pelo SCM, SSC e salto horizontal (SH) em todos os resultados apresentados, além de outras variáveis de desempenho (Granacher et al, 2015;Loturco et al, 2015;Loturco et al, 2016;Fonseca et al, 2017;Bianchi et al, 2019;Hammami et al, 2019;Ribeiro et al, 2019). Os outros 3 estudos (Villarreal et al, 2015;Beato et al, 2018;Ramirez-Campillo et al, 2018) realizaram intervenções mistas, envolvendo algum tipo de treinamento pliométrico, associado com outros métodos, como o de aceleração, de resistência de força, fundamentos do futebol e mudanças de direção e também comparados com outros GE ou GC.…”
Section: Resultsunclassified
“…Na maioria dos estudos, o TP produziu aumento sobre a IV. As intervenções mistas também proporcionaram efeitos positivos sobre a IV, conforme observados nos estudos de Villarreal et al (2015), Beato et al (2017), Campillo et al (2018) e Hammami et al (2019). A seguir, são apresentados os estudos incluídos na revisão agrupados de acordo com os tipos de intervenções e as variáveis analisadas.…”
Section: Discussionunclassified